2018
DOI: 10.3389/fmicb.2018.00942
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Major Pilin Subunit Genes Among Atypical Enteropathogenic Escherichia coli and Influence of Growth Media on Expression of the ecp Operon

Abstract: Atypical enteropathogenic Escherichia coli (aEPEC) strains are unable to produce the bundle-forming pilus (BFP), which is responsible for the localized adherence pattern, a characteristic of the pathogenicity of typical EPEC strains. The lack of BFP in aEPEC strains suggests that other fimbrial or non-fimbrial adhesins are involved in their adhesion to the host cells. The aim of this study was to investigate the distribution of major subunit fimbrial genes known to be important adherence factors produced by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Some E. coli strains, contain another type of fimbria, long polar fimbriae (LPF), encoded by the conserved gene lpfA 23,24. We found that 41.24% of the E. coli isolates carried lpfA , which is similar to the frequency (50%) reported in Mexico 25. Initial studies conducted on human biopsy samples have suggested that adherence and the attaching and effacing lesion caused by E. coli do not require LPF 24.…”
Section: Discussionsupporting
confidence: 71%
“…Some E. coli strains, contain another type of fimbria, long polar fimbriae (LPF), encoded by the conserved gene lpfA 23,24. We found that 41.24% of the E. coli isolates carried lpfA , which is similar to the frequency (50%) reported in Mexico 25. Initial studies conducted on human biopsy samples have suggested that adherence and the attaching and effacing lesion caused by E. coli do not require LPF 24.…”
Section: Discussionsupporting
confidence: 71%
“…The mPCR was designed to detect genes found in six well-established pathogenic E. coli pathotypes as follows: gene daaE for diffusely adherent E. coli (DAEC); aaiC and aggR for enteroaggregative E. coli (EAEC); ipaH for enteroinvasive E. coli (EIEC); eae and/or bfpA for enteropathogenic E. coli (EPEC); lt and/or st for enterotoxigenic E. coli (ETEC); and stx and/or eae for Shiga-toxin producing E. coli (STEC), as described before [20]. We further categorized EPEC as typical EPEC (eaeA+ bfpA+) or atypical EPEC (eaeA+ bfpA-) [20,25]. Also, EAEC were further subtyped in typical EAEC (aggR+) or atypical EAEC (aggR-, aaiC+) [26].…”
Section: Microbiologic Methodsmentioning
confidence: 99%
“…coli (STEC), as described before [ 20 ]. We further categorized EPEC as typical EPEC ( eaeA + bfpA +) or atypical EPEC ( eaeA + bfpA -) [ 20 , 25 ]. Also, EAEC were further subtyped in typical EAEC ( aggR+ ) or atypical EAEC ( aggR- , aaiC+ ) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most farm animals, including ruminants, harbour foodborne pathogens [ 3 , 27 , 28 , 29 ]. In addition, intensively reared beef and dairy animals tend to be housed in large numbers and this may promote proliferation and dissemination of foodborne pathogens into the environment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%